2020
DOI: 10.1186/s12889-020-09136-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with catastrophic total costs due to tuberculosis under a designated hospital service model: a cross-sectional study in China

Abstract: Background: Certain districts and counties in China designated local general hospital as the designated hospital for tuberculosis (TB) management after the promulgation of the Law of Practicing Physicians in 2009. To our knowledge, there is limited research on catastrophic payments of TB patients under this service model, often with inconsistent conclusions. In addition, there has been no published studies from China using the updated 2018 World Health Organization (WHO) definition of catastrophic total costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 26 publications
2
39
0
Order By: Relevance
“…6 Although HIV infection, tuberculosis and mental health conditions are common comorbidities in patients with T2DM, [31][32][33][34] these were not the most common comorbidities in this study. The prevalences of these infectious diseases are low in Ningbo, [35][36][37][38] and there are chances that mental health conditions were under-reported. It should also be noted that infectious diseases and mental health conditions as index conditions are treated in other specialised hospitals in Ningbo.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although HIV infection, tuberculosis and mental health conditions are common comorbidities in patients with T2DM, [31][32][33][34] these were not the most common comorbidities in this study. The prevalences of these infectious diseases are low in Ningbo, [35][36][37][38] and there are chances that mental health conditions were under-reported. It should also be noted that infectious diseases and mental health conditions as index conditions are treated in other specialised hospitals in Ningbo.…”
Section: Discussionmentioning
confidence: 99%
“…25 In addition to the national costs surveys, many studies reported the incidence of catastrophic costs at the local level, such as district, province, or several provinces. 13,[26][27][28] Despite the various methods applied, the studies at the local level also suggest that the incidence of TB-related catastrophic costs remains high.…”
Section: Tuberculosis-related Catastrophic Costsmentioning
confidence: 99%
“…The proportion of the direct cost to the total cost at 20% addressed in 7 studies, ranged from 26% in Chittamany, 2020 [33] to 93% in Yang, 2020 [32]. Low proportions were observed in Fuady,…”
Section: Pooled Proportion Of Direct Cost In Mdrmentioning
confidence: 99%
“…With 63% pooled proportion, 95%CI [40-80%], I 2 = 96%, three studies measured the CTP at 40% [12,29,30] and after the sensitivity test the heterogeneity was I 2= 0, while the pooled proportion increased to 70%, 95%CI [64-76%]. Among drug sensitive and drug resistant TB, the proportion of direct cost to the total cost ranged from (33% to 65%) [15,30,33,37,41,47] and (26%-93%) [15,30,32,33,37,41,47] respectively.…”
Section: Pooled Proportion Of Ctp At 40%mentioning
confidence: 99%
See 1 more Smart Citation